The Different Response to an Acid Shock of Two Salmonella Strains Marks Their Resistance to Thermal Treatments - Clemente-Carazo, Marta; Leal, José-Juan; Huertas, Juan-Pablo; Garre, Alberto; Palop, Alfredo; Periago, Paula M. (Frontiers in Microbiology, 2021)
Microbial cells respond to sub-lethal stresses with several physiological changes to increase their chance of survival. These changes are of high relevance when combined treatments (hurdle technology) are applied during food production, as the cells surviving the first hurdle may have greater resistance to subsequent treatments than untreated cells. In this study, we analyzed if Salmonella develops increased resistance to thermal treatments after the application of an acid shock. We compared the heat resistance of acid-shocked (pH 4.5 achieved with citric acid) Salmonella cells with that of cells maintained at pH 7 (control cells). Thermal treatments were performed between 57.5 and 65ºC. We observed a differential response between the two strains studied. Acid-shocked cells of Salmonella Senftenberg exhibited reduced heat resistance, e.g., for a treatment at 60.0°C and pH 7.0 the time required to reduce the population by 3 log cycles was lowered from 10.75 to 1.98 min with respect to control cells. Salmonella Enteritidis showed a different response, with acid-shocked cells having similar resistance than untreated cells (the time required to reduce 3 log cycles at 60.0ºC and pH 7.0 was 0.30 min for control and 0.31 min for acid-shock cells). Based on results by differential plating (with or without adding the maximum non-inhibitory concentration of NaCl to the recovery medium), we hypothesize that the differential response between strains can be associated to sub-lethal damage to the cell membrane of S. Senftenberg caused by the acid-shock. These results provide evidence that different strains of the same species can respond differently to an acid-shock and highlight the relevance of cross-resistances for microbial risk assessment.